2019
DOI: 10.1111/socf.12540
|View full text |Cite
|
Sign up to set email alerts
|

#BlackLivesMatter: Innovative Black Resistance

Abstract: Since 2013, extrajudicial police killings of black people have captured the attention of U.S. and international media, substantially because of the work of leaders in the Black Lives Matter (#BLM) movement. #BLM is simultaneously a group of localized organizations and a broad online social movement. In this article, we examine the #BLM movement in detail, with particular emphasis on the following aspects of the movement: (1) its innovative organizational practices and social media use; (2) its accent on black … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 41 publications
0
37
0
3
Order By: Relevance
“…Poell and Borra do insist that activist use of social media closely resembles the decades-long phenomenon of underground and alternative newspapers, weeklies, and broadcasts that contested hegemonic narratives in mainstream journalism (Poell & Borra, 2011). And as Nummi, Jennings, and Feagin write (Numm, Jennings, & Feagin, 2019), the counter-framing of Black experiences that the Black Lives Matter movement offers is the latest manifestation in a long history of Black journalism that counters mainstream media accounts. Research into social-mediated protest reporting has identified several key roles that such media potentially play in supplanting traditional journalism in protest situations.…”
Section: Protester Reporting As Culturementioning
confidence: 99%
“…Poell and Borra do insist that activist use of social media closely resembles the decades-long phenomenon of underground and alternative newspapers, weeklies, and broadcasts that contested hegemonic narratives in mainstream journalism (Poell & Borra, 2011). And as Nummi, Jennings, and Feagin write (Numm, Jennings, & Feagin, 2019), the counter-framing of Black experiences that the Black Lives Matter movement offers is the latest manifestation in a long history of Black journalism that counters mainstream media accounts. Research into social-mediated protest reporting has identified several key roles that such media potentially play in supplanting traditional journalism in protest situations.…”
Section: Protester Reporting As Culturementioning
confidence: 99%
“…The recent rise of citizen journalism, activist movements like Black Lives Matter, and organized filming practices like copwatching present police with modern challenges in legitimizing violence amidst intensifying public scrutiny (Ray et al., 2017; Stuart, 2011). These activist initiatives leverage social media to contest police violence by disseminating videos, sharing information, and mobilizing supporters (Brown, 2016; Jackson & Foucault Welles, 2015; Nummi et al., 2019).…”
Section: Police In the Age Of Social Mediamentioning
confidence: 99%
“…As police departments seek contemporary tools to manage controversial police violence, scholarship has primarily focused on the digital strategies of social activists to publicize it. The rise of citizen journalism and social media platforms have significantly advanced the ability of social movements to capture, circulate, and call into question the legitimacy of various police practices (Brown, 2016; Jackson & Foucault Welles, 2015; Nummi et al., 2019). For example, studies on movements like Black Lives Matter have begun unpacking how social media democratizes information sharing and news production to spread awareness and expose problematic policing (Ray et al., 2017).…”
mentioning
confidence: 99%
“…Nearly a half million people in over 550 places across the US protested on 6 June 2020 and 15-26 million people have participated in Black Lives Matter (BLM) demonstrations since the murder of George Floyd (Buchanan et al 2020). As Jozie Nummi et al (2019Nummi et al ( : 1043 point out: 'This historical resistance is necessary because in the U.S. case, systemic racism is based on a broad white racial frame (worldview) that penetrates all social institutions, public consciousness, and political bodies.' The 2020 protests for racial justice in the US have come at the confluence of the global COVID-19 pandemic, encroaching climate crisis, intensifying white supremacist violence, and massively growing inequality.…”
Section: Black Lives Matter and The Radical Imaginationmentioning
confidence: 99%
“…This perspective viewed the marketplace as the source of competition and excellence, but also rendered the economy of oppression invisible through an ahistorical view of how capitalism emerged in the US. White wealth was extracted from the enslaved labor of black bodies, siphoned from the exploited work of new immigrants and transferred from stolen Indigenous lands (Nummi et al 2019). As described in the previous section, racialized structures of social citizenship maintained firm barriers that mitigated against leveling the playing field of opportunity.…”
mentioning
confidence: 99%